Implementasi Sistem E-Court Dalam Mewujudkan Asas Sederhana, Cepat, Dan Biaya Ringan Di Pengadilan Negeri - Restu Teguh Imani; Elsa Siffa Nabillah Nurlailatri; Printa Dewi Uma Azzahra; Lintang Zufar Satyanagama; Nimas Calista Anggita; Destri Tsurayya Istiqamah (International Forum of Researchers and Lecturers, 2024)
The increasingly rapid development of technology makes it easier for humans to receive information and to carry out various jobs just by using sophisticated technology. The impact of these developments also affects the legal field. Indonesia has also begun to upgrade its judicial system through PERMA Number 7 of 2022 which regulates the Electronic Administration of Cases and Trials in Courts issued by the Supreme Court so that every Court begins to use an electronic court justice system with the aim of the supreme court's mandate to ensure that the principles of trials are simple, fast , and low cost can be achieved. Therefore, this writing was carried out by the author to find out about the implementation of e-court in realizing the principles of simple, fast and low-cost justice in trials at the District Court, and the author also observed the use of e-court which was also accessed by advocates in the author's place when participating in field work practices. This writing uses normative empirical research methods to determine the differences between Das Sollen and Das Sein and to compare the e-court system to the principles of civil justice in the form of simple, fast and low cost principles